Toward well-defined metal-polymer interfaces: Temperature-controlled suppression of subsurface diffusion and reaction at the calcium/poly(3- Hexylthiophene) interface - Bebensee, Fabian; Schmid, Martin; Steinrück, Hans-Peter; Campbell, C. T.; Gottfried, Michael (Journal of the American Chemical Society, 2010)
The thickness of the reaction zone at the interface between calcium and regioregular poly(3-hexylthiophene), which is one of the best performing metal/polymer combinations in photovoltaic devices, depends critically on the temperature of the polymer during the initial phase of metal deposition. It is shown that deposition at 130 K reduces the thickness of the reaction zone, an effect that also persists after warming to room temperature. © 2010 American Chemical Society.